Entrepreneurial Education and Self-employment: Does Entrepreneurial Self-efficacy Matter? - Kisubi, Moses Kisame; Bonuke, Ronald; Korir, Michael (SEISENSE Business Review, 2021)
The study sought to determine the mediating role of entrepreneurial self-efficacy in the relationship between entrepreneurship education and self-employment intentions. A cross-sectional and explanatory survey approach was employed using a systematic sampling technique. Data were collected from a sample of 458 undergraduate finalists from two Ugandan universities. Results of the study indicate that two predictors significantly influence self-employment intentions. Results also suggest that entrepreneurial self-efficacy partially mediates the relationship between entrepreneurship education and self-employment intentions. Curriculum developers should develop entrepreneurship curriculum content geared towards stimulation of self-employment intentions among learners via entrepreneurial self-efficacy. Second, educational and economic policymakers should design policies and programs like startup capital to enable graduates to realize their self-employment intentions. The study provides initial evidence on the mediating effect of entrepreneurial self-efficacy between entrepreneurship education and self-employment intentions.
Keywords: Entrepreneurship education, Entrepreneurial self efficacy, Self employment intentions, Students